On the third‐generation Calphad databases: An updated description of Mn. Issue 10 (23rd June 2015) - Bigdeli, Sedigheh; Mao, Huahai; Selleby, Malin
<x xml:space="preserve">Abstract</x> Aiming for better extrapolations and predictabilities of thermodynamic properties of materials, new thermodynamic models are implemented in the third‐generation Calphad databases. In these models, each term contributing to the Gibbs energy has an explicit physical meaning. Furthermore, descriptions of thermodynamic properties of materials are valid from 0 K up to high temperatures far above the melting point. As a starting point for the development of large self‐consistent third‐generation database, the new models in the present work are applied to the unary manganese system. Taking into account both the calculated first principles results and experimental data, thermodynamic model parameters are evaluated. Thermodynamic properties predicted using this description, agree very well with available data. The calculated properties vary smoothly in the whole temperature range, which is another important improvement compared to the second‐generation databases.